2019
DOI: 10.1097/mph.0000000000001707
|View full text |Cite
|
Sign up to set email alerts
|

Dosage of 6-Mercaptopurine in Relation to Genetic TPMT and ITPA Variants: Toward Individualized Pediatric Acute Lymphoblastic Leukemia Maintenance Treatment

Abstract: 6-mercaptopurine (6-MP) is the mainstay in pediatric acute lymphoblastic leukemia (ALL) maintenance treatment. Variants in genes coding for thiopurine S-methyl transferase (TPMT) and inosine triphosphate pyrophosphatase (ITPA) are known to influence 6-MP metabolism. We determined TPMT and ITPA genotype and enzyme activity and the mean 6-MP doses during maintenance treatment in 40 children treated for ALL according to the Dutch Childhood Oncology Group (DCOG)-ALL11 protocol in the Radboudumc Amalia Children’s H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The evidence that TPMT heterozygotes are associated with increased of 6-MP-induced myelotoxicity also backs up the compelling need for genotype this pharmacogenetic marker prior to starting 6-MP medication. A study by Kouwenberg et al (2020) suggested that before starting ALL maintenance treatment, the TPMT genotype should be considered as part of standard examination.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence that TPMT heterozygotes are associated with increased of 6-MP-induced myelotoxicity also backs up the compelling need for genotype this pharmacogenetic marker prior to starting 6-MP medication. A study by Kouwenberg et al (2020) suggested that before starting ALL maintenance treatment, the TPMT genotype should be considered as part of standard examination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ITPA genotyping has no predictive significance for the clarity and development of the AZA side effects ( van Dieren et al, 2005 ). In the Netherlands, the mean doses of 6-MP did not differ in ALL patients with or without ITPA variants ( Kouwenberg et al, 2020 ). Another study came to a similar conclusion ( Wahlund et al, 2020 ).…”
Section: Pharmacogenetics Of Thiopurinesmentioning
confidence: 96%
“…48,55 Although genotype-guided dosing of thiopurines is routinely performed in gastroenterology and rheumatology, it has particular importance in malignancies like acute lymphoblastic leukemia (ALL), in which thiopurines are part of standard curative regimens and agent substitution is not desirable. 133 The association between 6-mercaptopurine dosing, tolerance, and TPMT genotype was first established in a landmark study evaluating pediatric patients with leukemia who were receiving treatment on the St Jude Children's Research Hospital Protocol XII. 54 In that study, the specifically administered weekly doses were titrated based on blood counts during therapy, and only patients with severe toxicity or severe myelosuppression had doses omitted or decreased for a given week.…”
Section: Using Multigene Predictors In Germline Oncologymentioning
confidence: 99%
“…The most common inherited variant alleles are *2, *3A, and *3C; and an estimated 10% to 12% and 0.1% to 0.3% of the population are heterozygous carriers (with intermediate TPMT activity) or homozygous variant carriers (with absent TPMT activity), respectively 48,55 . Although genotype‐guided dosing of thiopurines is routinely performed in gastroenterology and rheumatology, it has particular importance in malignancies like acute lymphoblastic leukemia (ALL), in which thiopurines are part of standard curative regimens and agent substitution is not desirable 133 …”
Section: Using Multigene Predictors In Germline Oncologymentioning
confidence: 99%